Prevalence and Risk Factors for Spasticity After Stroke: A Systematic Review and Meta-Analysis - Zeng, Huangling; Chen, Jian; Guo, Yang; Tan, Sheng (Frontiers in Neurology, 2021)
Background: Spasticity is a common sequela of stroke. The incidence of poststroke spasticity (PSS) has not been systematically reviewed in recent years, and some risk factors remain debated. This systematic review and meta-analysis was conducted to determine the prevalence and risk factors for PSS. Methods: We searched electronic databases (PubMed, Embase, Cochrane Library, CNKI, WANFANG and CBM) inception to May 12, 2020. Observational studies summarizing the incidence or risk factors for PSS were included. Only cohort studies were enrolled in meta-analysis. For risk factors examined in at least three different studies, we combined effects into odds ratios (OR) and a 95% confidence interval (CI). Results: 1467 studies were retrieved and 23 were involved in meta-analysis. The incidence of spasticity after stroke was 25.3% and that after the first stroke was 26.7%. The incidence of spasticity after the first-ever stroke with paresis was 39.5%. The prevalence of disabling or severe spasticity (MAS ≥ 3) in stroke patients with paresis was 9.4% (95% CI 0.056 to 0.133), and severe spasticity was 10.3% (95% CI 0.058 to 0.149). Moderate to severe paresis (OR = 6.573, 95% CI 2.579 to 16.755, I2 = 0.0%), hemorrhagic stroke (OR = 1.879, 95% CI 1.418 to 2.490, I2 = 27.3%) and sensory disorder were risk factors for PSS. Conclusions: The incidence of PSS was significantly higher in stroke patients with paresis. Patients with moderate to severe paresis and sensory disorder should be closely followed up.